An evaluation of the clinical utility of mangled extremity severity score in severely injured lower limbs - Agarwal, Vipul; Agarwal, Sarina; Singh, Abhishek; Satani, Setu; Goel, Shewtank; Goyal, Pooja; Jhamnani, Rohit (International Journal of Research in Medical Sciences, 2016)
Background: The management of severe lower limb injury is one of the most controversial subjects in the field of Orthopedic surgery. While the advancement of sophisticated microsurgical reconstruction technique has created the possibility of successful limb salvage in even the most extreme cases, it has become painfully obvious that the technical possibilities are double-edged swords. The aim of study was to analyze and ascertain the clinical utility of mangled extremity severity score (MESS) in severely injured lower limbs. Methods: The current study was undertaken in the Department of Orthopedics among 50 patients who sustained high-energy injuries and approached a tertiary care center to seek care. The study design included both retrospective and prospective evaluation. Retrospectively 25 and prospectively 25 lower limbs in 54 patients with high-energy injuries were evaluated using mangled extremity severity score to assist in the decision-making process for the care of patients with such injuries. MESS served as study tool. Differences between the mean MESS scores for amputated and salvaged limbs were explored. Results: Crush injury of leg with fracture of tibia and fibula was observed in 78% of injured limbs. The most common mechanism of injury was high-energy trauma. Road traffic accidents accounted for 72% of patients. Mean hospitalization for primary amputation was 19.3 (8-26) days and for delayed amputation limbs was 36.6 (15-62) days and for salvaged limbs was 45.5 (14-128) days. In the prospective study, out of 7 injured limbs with a MESS score of equal or more than 7, 6 limbs were amputated and 1 limb was salvaged. Out of the remaining 18 injured limbs with a MESS score of less than 7, 17 limbs were successfully salvaged and one limb was amputated. In the retrospective study, 10 injured limbs with a MESS score of equal or more than 7 were amputated (mean score 8.4 with range of 10-8) and the remaining 15 injured limbs with a MESS score of less than 7 were salvaged (mean score 4.57 with range of (4-6)); suggesting a significant difference in the mean scores. Conclusions: MESS is a cost-effective, relatively simple and readily available scoring system, which assists the surgeon to identify variables that may ultimately influence the outcome of a severely traumatized extremity with arterial compromise due to high-energy injury.